Stress, Stressors, and Coping Strategies of Female Private School Teacher to Deal with Occupational Stress - Fasiha Shah; Azlinda Azman; Paramjit Singh Jamir Singh (Asian Social Work Journal, 2023)
Mental health is the least prioritized subject in Pakistan though stress, anxiety and depressive disorders have been indicated as root cause of several chronic disease. Stress arises when an individual observes that he/she cannot cope with the demands placed on them or perceives a threat to his well-being. However, utilizing effective coping strategies can help to manage stress. The current study is a quantitative cross-sectional study aimed to assess the prevalence of occupational stress, stressors, and coping strategies of female private school teachers (n=1,386) working in Hyderabad city. Data was analysed using SPSS version 22.0, descriptive analysis was calculated and p-value <0.05 was considered as significant. The results revealed that majority of teachers were experiencing higher level of occupational stress. The stressors of teachers were sorted as work-related distress, professional growth, managing their work within given time, inadequate salary, emotional and fatigue manifestations were more obvious for teachers. Teachers were found to use dysfunctional and emotional coping strategies most often. The study concluded that overall working conditions of private school teachers were observed challenging. There is immense need to promote healthy working environment for better performance of teachers and ultimately resulting in succeeding and advancing educational organizations.